Searching for cardioprotective microRNA families by bioinformatics analysis of cross-species transcriptomic datasets. (10th June 2022) - Agg, B; Benczik, B; Kemendi, BV; Makkos, A; Petervari, M; Varga, ZV; Ferdinandy, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This study was supported by the National Research, Development and Innovation Office of Hungary (NKFIA; NVKP-16-1-2016-0017 National Heart Program) and the Thematic Excellence Programme (2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Molecular Biology thematic programmes of the Semmelweis University. Introduction: There is a growing body of evidence that changes in cardiac microRNA expression pattern plays an important role in cardioprotective cellular signaling. Purpose: Our aim was to identify evolutionarily conserved cardioprotective microRNA (protectomiR) families with a high probability of translation into human clinical practice. Methods: Global cardiac microRNA expression profiles were measured in both a rat and a porcine model of myocardial infarction with or without ischemic preconditioning and postconditioning by microarray and high-throughput polymerase chain reaction, respectively. A software developed by our team was used to identify cross-species microRNA families (i.e. microRNAs with identic seed sequence) with cardioprotective expression patterns. By selecting experimentally validated human target genes from the miRTarBase database we built a microRNA family-target interaction network by the miRNAtarget.com software. Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed on the selected target genes. Results: Due to potential patenting, microRNAs and microRNA families were anonymized. We identified 7 microRNA families, showing cardioprotective expression pattern. Based on the analysis of the microRNA family-target network, expression change of the target hubs were predicted to be consistent with previously described changes in pathways with high relevance in cardioprotection (e.g. positive regulation of TGF-beta, HIF-1, PI3K-Akt signaling pathways). Conclusion: By an unbiased transcriptomics and bioinformatics based approach we successfully identified microRNA families with robust cross-species protectomiR expression pattern and targets involved in well-established cardioprotective pathways. These cardioprotective microRNA families are of high translational value for human clinical application.